Statistical data processing of flight safety indices of Ukrainian aviation - Холявкіна, Т. В.; Сукач, О. М. (Problems of Informatization and Control, 2009)
The problems of flight safety monitoring on the regular basis and statistical data analysis peculiarity in civil aviation of Ukrainian are considered in the article. The methods and algorithms of statistical indices and their trust limit calculation are designed. Trustworthiness increasing methods of statistical calculation with consideration of regional peculiarity and operating conditions of Ukrainian aviation are shown